Leading Cities A Global Review of City Leadership - Rapoport, Elizabeth (UCL Press, 2019)
Leading Cities is a global review of the state of city leadership and urban governance today. Drawing on research into 202 cities in 100 countries, the book provides a broad, international evidence base grounded in the experiences of all types of cities. It offers a scholarly but also practical assessment of how cities are led, what challenges their leaders face, and the ways in which this leadership is increasingly connected to global affairs. Arguing that effective leadership is not just something created by an individual, Elizabeth Rapoport, Michele Acuto and Leonora Grcheva focus on three elements of city leadership: leaders, the structures and institutions that underpin them, and the tools used to drive change. Each of these elements are examined in turn, as are the major urban policy issues that leaders confront today on the ground. The book also takes a deep dive into one particular example of tool or instrument of city leadership - the strategic urban plan.